It's time to address fear of cancer recurrence in family caregivers: usability study of an virtual version of the Family Caregiver—Fear Of Recurrence Therapy (FC-FORT) - Lamarche, Jani; Cusson, Angélica; Nissim, Rinat; Avery, Jonathan; Wong, Jiahui; Maheu, Christine; Lambert, Sylvie D.; Laizner, Andrea M.; Jones, Jennifer; Esplen, Mary Jane; Lebel, Sophie (Frontiers in Digital Health, 2023)
Background Family caregivers of cancer survivors experience equal or greater levels of fear of cancer recurrence (FCR) than survivors themselves. Some interventions have demonstrated their ability to reduce FCR among cancer survivors and dyads (patient and caregivers). However, to date, no validated intervention exists to focus solely on family caregiver's FCR. Objectives This study aimed to (1) adapt the evidence-based in-person Fear Of Recurrence Therapy (FORT) for family caregivers (referred here in as FC-FORT) and to a virtual delivery format and (2) test its usability when offered virtually. Methods The adaptation of FC-FORT was overseen by an advisory board and guided by the Information Systems Research Framework. Following this adaptation, female family caregivers and therapists were recruited for the usability study. Participants took part in 7 weekly virtual group therapy sessions, a semi-structured exit interview and completed session feedback questionnaires. Therapists were offered a virtual training and weekly supervision. Fidelity of treatment administration was assessed each session. Quantitative data were analyzed using descriptive statistics. Exit interviews were transcribed verbatim using NVivo Transcription and coded using conventional content analysis. Results were presented back to the advisory board to further refine FC-FORT. Results The advisory board (n = 16) met virtually on 7 occasions to adapt FC-FORT (i.e., patient manuals, virtual format) and discuss recruitment strategies. Minor (e.g., revised text, adapted materials to virtual format) and major adaptations (e.g., added and rearranged sessions) were made to FC-FORT and subsequently approved by the advisory board. Four family caregivers and three therapists took part in the first round of the usability testing. Six family caregivers and the same three therapists took part in the second round. Overall, participants were very satisfied with FC-FORT's usability. Qualitative analysis identified 4 key themes: usability of FC-FORT, satisfaction and engagement with content, group cohesion, and impact of FC-FORT. All participants indicated that they would recommend FC-FORT to others as is. Conclusions Using a multidisciplinary advisory board, our team successfully adapted FC-FORT and tested its usability using videoconferencing. Results from this study indicate that the efficacy and acceptability of FC-FORT are now ready to be tested in a larger pilot study.